Effects of intranasal oxytocin on the self-perception and anxiety of singers during a simulated public singing performance: A randomized, placebo-controlled trial - Osório, Flávia de Lima; Espitia-Rojas, Gleidy Vannesa; Aguiar-Ricz, Lilian Neto (Frontiers in Neuroscience, 2022)
Professional musicians experience intense social exposure and high levels of preoccupation with their performance and potential negative reactions from the audience, which favor anxiety. Considering that oxytocin (OXT) has a potential therapeutic effect on anxiety, cognitive processes, and decreased psychosocial stress, this study’s objective was to assess the effects of a single dose of 24 UI of intranasal OXT among professional singers, during a public singing simulation test, on self-rated performance and mood. This crossover, randomized, double-blinded, placebo-controlled trial addressed 54 male singers with different levels of musical performance anxiety (42% high). The participants took part in different phases of a simulated public singing performance and completed instruments rating their performances (Self Statements During Public Performance- State version) and mood (Visual Analogue Mood Scale). Data were analyzed using ANOVA 2 × 2 for crossover trials. The results show that the use of OXT during the performance and immediate post-stress favored more positive (effect size: d > 1.04) and less negative assessments of musical performance (effect size: d > 1.86) than when placebo was used. No treatment effects were found in any VAMS subscales, indicating no direct anxiolytic effects. The conclusion is that OXT can minimizes social stress, especially during performances. This finding is exploratory and, if confirmed in future studies, may have relevance for musicians, especially those who constantly experience and recognize the impact of negative and catastrophic thoughts on performance and professional activities. Clinical Trial Registration [https://ensaiosclinicos.gov.br/rg/RBR-5r5sc5], identifier [RBR-5r5sc5].